Efficacy of Endophytic Bacteria as Entomopathogens against Spodoptera frugiperda (Lepidotera: Noctuidae) on Corn (Zea mays L.) - Kurniawati Kurniawati; Arika Purnawati; Wiwin Windriyanti (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
The fall armyworm (Spodoptera frugiperda) poses a problem for corn plants (Zea mays L.). The use of endophytic bacteria Bacillus sp. as an entomopathogen is expected to control the S. frugiperda pest. This study aims to determine the effective concentration of the bacteria and the active compounds produced by Bacillus sp. strain Bth 22 in controlling S. frugiperda. The research was conducted from August to October 2024 at the Plant Health Laboratory of the Faculty of Agriculture, UPN "Veteran" East Java, and the Airlangga Research Hub in Surabaya. The study was designed using a completely randomized design (CRD) with bacterial concentration treatments of 0% (control), 10%, 15%, 20%, 25%, 30%, and 35%, repeated five times. Observational parameters included mortality rate, number of pupae and imago formed, as well as the mechanisms and compounds produced by Bacillus bacteria based on HPLC and FT-IR tests. The application of Bacillus sp. Bth-22 affected the mortality parameters, the number of pupae formed, and the number of imago formed. The Bacillus sp. Bth-22 bacteria produced metabolites in the form of hydrocarbon derivatives and amide group compounds, disrupting metabolism and digestion, leading to the mortality of S. frugiperda. Keywords: Entomopathogen, Metabolite compounds, Spodoptera frugiperda, Zea mays